Great St. Louis bank robbery Gold. - McQueen, Steve, 1930-1980.; Denton, Graham; Clarke, David, 1908-2004.; Guggenheim, Charles; Stix, John, 1920-2004.; Moore, Roger, 1927-; York, Susannah; Milland, Ray.; Hunt, Peter, 1925-2002.; Smith, Wilbur A. ([S.l. : s.n., 2010)
The great St. Louis bank robbery: This dramatic recreation of a failed bank heist was filmed in the original locations where the true-life event occurred, and was cast with the actual policement, bank customers and area residents who were involved in the affair, giving the production an intense and gritty realism. An expelled college football hero joins a hurriedly formed gang of ex-convicts planning a bank robbery, but personal jealousies and frustrations among the four men doom the operation.
Gold: A South African mining engineer exposes a plot to control the price of gold on the world market. He also falls in love with the boss's granddaughter.
Great St. Louis bank robbery (1960, 86 min.) -- Gold (1974, 118 min.).
Title from container.
Gold: Based on the novel Gold mine by Wilbur Smith.
Great St. Louis bank robbery: Steve McQueen, Graham Denton, David Clarke.
Gold: Roger Moore, Susannah York, Ray Milland.
DVD, region free; Dolby digital.
Keywords: Bank robberies; Gold mines and mining; Saint Louis (Mo.); South Africa; Feature films